Marketing Strategy of Herbal Spice Drink Products at the Spice House Cafe of Anwar Medika General Hospital - Elis Anita Farida (IQTISHADequity jurnal MANAJEMEN, 2022)
ABSTRACTThe relationship between business strategies for introducing business products is very close, especially for new products for health. Business development and business strategies need to be carried out to create new markets, develop products, and complement existing products. The purpose of this study is to analyze product strategy in introducing herbal beverage products at the Rumah Rempah Rumah Saku General Anwar Medika cafe to assist in strengthening product identity and introducing stronger business products. The results of the strategy used for herbal spice drink products as new products were based on the application of SWOT analysis (Strength/”S”, Weaknes/“W”, Opportunity/”O”, and Treats/”T”). Strength (Strength) – Opportunity (Opportunity) as a consideration in the strategy of prioritizing product quality, product benefits, marketing and competition (online), discounts, and buying one get one. Weaknesses: opportunities to seek strategic opportunities based on existing weaknesses, analysis of market conditions, packaging, building a business through product reviews, and collaboration with business partners. Strength Strategy – threats to analyze to find product superiority based on product quality and benefits, as well as other considerations in terms of price and raw material aspects. Weakness strategy: The treatment for analyzing weaknesses and threats consists of research and development strategies, product patents, services, and product evaluation. The application of marketing strategies can increase customer interest in building trust in the product, product quality, and business sustainability at the Spice House of Anwar Medika General Hospital.